Symbolic Concepts of Culture and the Problem of Language of Cinema - Tasbolatuly, A.; Hejazi, S.; Ismagambetova, Z.N. ("Акад. Е.А. Бөкетов ат. Қарағанды ун-ті" КЕАҚ баспасы, 2023)
One of the urgent tasks in culturological science is the study of the problem of the language of cinema in the context of culture. An important role in the formation of the language of cinema was played by theoretical and methodological symbolic studies of culture. In this regard, in this article, the authors consider the main provisions and tasks of the symbolic study of culture, the formation of symbolism in the construction of the language of literature, poetry, in general, their role in the formation of a symbolic understanding of cultural phenomena in human life. The authors of this article analyze the influence of symbolic studies of culture on the formation of the language of cinema. The main objectives of the article are to determine the theoretical contribution of symbolic studies in the study of culture, to show their influence on the formation of the language of cinema. To this end, the authors analyzed the main works of scientists involved in the study of culture from the standpoint of a symbolic approach. The novelty of the study lies in determining the role of symbolic studies of culture in shaping the language of cinema. Determining the contribution of symbolic concepts to the study of culture, the authors of the article emphasize the influence of these studies on the formation of the language of cinema, but at the same time, the construction of a symbolic language.
Мәдениеттің символдық концептілері және кино тілі
Символические концепции культуры и проблема языка кино
Keywords: symbols; symbolic concepts of culture; sign; cinema; film language; symbolism; film symbols; symbolic film language of culture; literary language